2022
DOI: 10.3389/fcvm.2022.818789
|View full text |Cite
|
Sign up to set email alerts
|

Serum IL-1, Pyroptosis and Intracranial Aneurysm Wall Enhancement: Analysis Integrating Radiology, Serum Cytokines and Histology

Abstract: Background and PurposeAneurysm wall enhancement (AWE) is correlated with the rupture and growth risk of unruptured intracranial aneurysms (UIAs). Pyroptosis is a proinflammation mode of lytic cell death, mediated by pyroptosis-related proteins, i.e., gasdermin D and interleukin 1 β (IL-1β). Integrating serum cytokines and histology, this study aimed to investigate the correlation between AWE and pyroptosis in UIAs.MethodsUIA patients receiving microsurgical clipping were prospectively enrolled from January 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…AWE on HR-VWI has been used as an imaging marker for vessel wall inflammation and aneurysm instability in patients with UIA. Recent studies showed the association of inflammatory blood biomarkers with AWE on HR-VWI in UIA patients (9)(10)(11)(12)(13). The plasma concentration of anti-inflammatory cytokine interleukin (IL)-10 in the aneurysm sac decreased in UIA with AWE (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AWE on HR-VWI has been used as an imaging marker for vessel wall inflammation and aneurysm instability in patients with UIA. Recent studies showed the association of inflammatory blood biomarkers with AWE on HR-VWI in UIA patients (9)(10)(11)(12)(13). The plasma concentration of anti-inflammatory cytokine interleukin (IL)-10 in the aneurysm sac decreased in UIA with AWE (10).…”
Section: Discussionmentioning
confidence: 99%
“…There was histological inflammation infiltration in aneurysm tissues with AWE. The serum IL-1β, IL-1RA, and IL-1RA/IL-1β ratio were associated with the inflammation-related proteins in aneurysm tissues ( 13 ). These results suggested that systematic inflammatory cytokines in the peripheral blood correlated with inflammatory factors in aneurysm tissues with AWE on HR-VWI, which may be a potential biomarker for aneurysm instability in UIA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interleukin-1 (IL-1) has been reported to play an important role in the immune and inflammatory responses in cerebrovascular diseases [ 18 , 19 ]. IL-1 β is one of the 3 members of the IL-1 family, which was highly expressed in intracranial aneurysm samples [ 20 ]. Previous studies showed the changes in TNF- α are related to human cerebral aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al ( 21 ) prospectively investigated the correlation between imaging, cytokines, and histological samples of patients with UIA. They demonstrated that aneurysm wall enhancement was associated with pyroptosis in UIA tissues and pyroptosis-related serum cytokines such as the inflammatory cytokine IL-1β and anti-inflammatory cytokine IL-1 receptor antagonist (IL-1.ra).…”
Section: Application Of Peripheral Blood Biomarkers In Unruptured Int...mentioning
confidence: 99%